An African American pastor before and during the American Civil War the literary archive of Henry McNeal Turner. Vol. 2, The chaplain writings - Turner, Henry McNeal, 1834-1915.; Johnson, Andre E. (Lewiston, N.Y. : Edwin Mellen Press, 2012)
Henry McNeal Turner (1834-1915) was one of America's earliest black activists and social reformers. This book recovers a lost voice within American and African American rhetorical history.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Turner, Henry McNeal, -- 1834-1915.; Turner, Henry McNeal, -- 1834-1915 -- Diaries; Turner, Henry McNeal, -- 1834-1915 -- Correspondence; Turner, Henry McNeal, -- 1834-1915 -- Sermons; African Americans -- Social conditions -- 19th century -- Sources; United States -- Social conditions -- 19th century -- Sources; African Methodist Episcopal Church -- History -- 19th century -- Sources; African Methodist Episcopal Church -- Bishops -- Biography; African Methodist Episcopal Church -- History -- 19th century -- Sources; Turner, Henry McNeal, 1834-1915 -- Corrrespondence; Turner, Henry McNeal, 1834-1915 -- Diaries; Turner, Henry McNeal, 1834-1915 -- Sermons; Turner, Henry McNeal, 1834-1915.; Literature; Religion; RELIGION / Christianity / Methodist; BIOGRAPHY & AUTOBIOGRAPHY / Religious; Electronic books